[Donnybrook Fair] - MacManus, Henry, 1810-1878; Hall, S. C., Mrs., 1800-1881 (1840)
Crowds gathered at a fair in Donnybrook showing games, stalls and amusements.
Attributed to Henry MacManus.
Catalogue of Irish Topographical Prints and Original Drawings / Rosalind M. Elmes ; New edition revised and enlarged by Michael Hewson - Dublin : Malton Press, 1975
Ireland: its scenery, character, &c / Mr. & Mrs. S. C. Hall - London: How and Parsons, 1841-43
Keywords: Fairs -- Ireland -- Donnybrook (Dublin) -- 1830.; Donnybrook (Dublin, Ireland); Pencil drawings -- Irish -- 1830-1840.